5-HT1A receptor sensitivity in major depression. A neuroendocrine study with buspirone. - Cowen, P; Power, A; Ware, C; Anderson, I (1994)
The hypothermic, growth hormone and corticotrophin (ACTH) responses to the 5-HT1A receptor agonist buspirone (30 mg orally) were measured in 20 unmedicated patients with major depression and 20 healthy controls. Compared with the controls, the hypothermic responses of the depressed patients to buspirone were significantly attenuated, particularly in patients with melancholic depression. In contrast, the responses of growth hormone and ACTH to buspirone were unchanged. The data suggest that major depression may be associated with impaired sensitivity of 5-HT1A autoreceptors but that the function of the post-synaptic 5-HT1A receptors that mediate growth hormone and ACTH release is unaltered. Within the limitations that attend the use of buspirone as a 5-HT1A probe, our data suggest that the decrement in serotonin neurotransmission at post-synaptic 5-HT1A receptors in depression is due to decreased serotonin release rather than impaired responsivity of post-synaptic 5-HT1A receptors.